ANALISIS LITERATUR TERKINI TENTANG INOVASI MANAJEMEN DALAM EKONOMI DIGITAL: IMPLIKASI DAN TREN GLOBAL - Muhammad Hendra; Loso Judijanto; Eka Suci Apriliyani; Mirza A Malik; Muhammad Sukron Fauzi (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This study aims to identify and analyze current trends in management innovation that have emerged as a response to digital transformation in the global economy. The primary focus is to understand how managerial innovations are adapted to leverage digital technology and how this adaptation impacts organizational performance and business strategies. This research is a literature review, a systematic method for evaluating, synthesizing, and analyzing existing literature on a particular topic. A literature review involves a comprehensive examination of scholarly works, articles, books, and other academic sources to understand the latest developments, trends, and issues related to a specific field of study. The findings indicate that the digital economy involves the integration of information and communication technologies, including the internet, big data, and artificial intelligence, to enhance efficiency and innovation in business processes. This transformation alters traditional business models and creates new opportunities. Digital management innovation includes the adoption of new technologies such as cloud computing and data analytics, as well as structural changes within organizations to improve effectiveness and responsiveness to the market. Current trends include the adoption of cloud-based technologies, the use of big data, and automation with AI, with regional variations in technology adoption and responses to government policies. A deep understanding of both local and global contexts is crucial for tailoring managerial strategies and effectively leveraging technological opportunities.